2000
DOI: 10.7326/0003-4819-133-1-200007040-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclooxygenase-2 Inhibition on Renal Function in Elderly Persons Receiving a Low-Salt Diet

Abstract: The effects of COX-2 inhibition on renal function are similar to those observed with nonselective NSAIDs. Thus, COX-2 seems to play an important role in human renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
175
1
8

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(188 citation statements)
references
References 19 publications
4
175
1
8
Order By: Relevance
“…The majority of renal events are dose dependent and are due either to the occurrence of oedema or an increase in blood pressure. Similar renal adverse effects have also been described for celecoxib 53 and rofecoxib, 54 raising the question of whether these effects are mediated by COX-2 inhibition in the kidney. In view of these findings and as in treatment with other 'coxibs' and traditional NSAIDs, it is recommended that the administration of valdecoxib be accompanied by close monitoring of renal function, especially in subjects in whom renal function is highly dependent on the production of prostaglandins (e.g.…”
Section: Renal Effectsmentioning
confidence: 58%
“…The majority of renal events are dose dependent and are due either to the occurrence of oedema or an increase in blood pressure. Similar renal adverse effects have also been described for celecoxib 53 and rofecoxib, 54 raising the question of whether these effects are mediated by COX-2 inhibition in the kidney. In view of these findings and as in treatment with other 'coxibs' and traditional NSAIDs, it is recommended that the administration of valdecoxib be accompanied by close monitoring of renal function, especially in subjects in whom renal function is highly dependent on the production of prostaglandins (e.g.…”
Section: Renal Effectsmentioning
confidence: 58%
“…Successful agents include nonsteroidal antiinflammatory drugs (NSAIDs) and intraarticular corticosteroid and hyaluronate injections. Despite the development of cyclooxygenase 2-selective NSAIDs, which can reduce the risk of gastrointestinal bleeding compared with nonselective NSAIDs (1,2), significant concerns remain regarding the systemic toxicities of NSAIDs (3)(4)(5). Intraarticular therapies are, for the most part, devoid of significant systemic toxicity but may have detrimental effects on joint integrity (6,7).…”
mentioning
confidence: 99%
“…9 In a randomized, controlled trial in elderly persons receiving a low-salt diet, it has been shown that the effects of rofecoxib COX-2 inhibition on renal function were similar to those observed with nonselective NSAIDs (indomethacin). 10,11 Others, however, have reported that COX-2 inhibition in healthy elderly subjects may spare renal hemodynamic function, although the effects on sodium excretion, as well as urinary prostaglandin E2 and 6-keto-prostaglandin F1 alpha excretion, appear to be 12 Other manifestations of sodium retention (such as pleural effusions) have been reported with the use of rofecoxib. 13 In general, it is the consensus that COX-2 selective inhibitors, like other NSAIDs, must be used cautiously or not at all in patients with predisposing diseases such as chronic renal failure, severe cardiac disease, and hepatic failure.…”
Section: Side Effects Of Cox-2 Inhibitorsmentioning
confidence: 99%